Impacts of Field and Laboratory Long-Term Aging on Asphalt Binders. Issue 8 (August 2022) - Singhvi, Punit; Mainieri, Javier J. García; Ozer, Hasan; Sharma, Brajendra Kumar; Al-Qadi, Imad L.; Morse, Kelly L.
Asphalt binder aging accelerates cracking of flexible pavement. Quantifying the extent of binder aging allows the formulation and selection of appropriate binders for flexible pavement applications. Asphalt binder aging depends on climatic exposure, asphalt concrete field-surface density, and binder chemistry. The aim of this work was to select a laboratory-aging protocol to represent realistic field aging in Illinois. Binders were extracted from field cores aged from eight to 31 years. Extracted binders were tested for rheology and chemical characteristics. Small- and large-strain rheological parameters were determined. In addition, chemical functional groups and molecular weight distribution of extracted binders were evaluated. Effects of aging across pavement depth were also investigated. Double pressure-aging vessel (PAV) was identified as a suitable laboratory long-term aging protocol to represent eight to 12 years of aging for flexible pavements in Illinois. Thresholds were proposed for selected small- and large-strain rheological parameters representing realistic field aging. These thresholds may be used for binder selection and procurement to ensure the binder's long-term performance. Furthermore, chemical analysis on extracted binders showed that only specific carbonyl functional groups are affected by field aging.